Determination of the mineral composition in agroindustrial by-products used in animal nutrition, by neutron activation analysis - Filho, José Cleto da Silva; Armelin, Maria José Aguirre; Silva, Aliomar Gabriel da (Pesquisa Agropecuaria Brasileira, 1999)
This study aimed to analyze some agroindustrial by-products used to feed animals in order to identify the presence of the main minerals. Samples of cotton seed meal, rice, canola, soybean and wheat; fish meal, feather meal, meat meal, feather plus viscera meal; rinds of cotton, rice, orange; citrus pulp and tomato residue were collected in different sites of production of the by-products. The method of analysis used was the neutron activation followed by gamma ray spectrometry. The levels of minerals found in all samples were compared with the levels commonly found in forages. The mineral concentration, even those of the toxic elements, as As, Cd and Hg, was at low level and did not exceed the maximum tolerable levels for domestic animals.